ANALYSIS OF THE INSURANCE MARKET OF THE REPUBLIC OF UZBEKISTAN AND PROBLEMS IN THE FIELD - Islamov Shukhratjon Tuychibayevich (Journals Park Publishing, 2022)
In the article, the indicators of targeted development of the insurance market of Uzbekistan in the future are analyzed and their classification is presented. Scientific conclusions and recommendations on the further improvement of the country's insurance market have been formulated.
Keywords: insurance payment, insurance premium, insurance market structure, insurance infrastructure, risk